The Integration of EFA and CFA: One Method of Evaluating the Construct Validity (Global Journal of Human-Social Science, 2015)
The approach of evaluating the construct validity has little development in the past one hundred years. As the theory of EFA and CFA had been proposed and refined these years we can find that they are good methods to evaluating the construct validity. This paper give a concepts of construct validity firstly and then analyzed the shortcoming of existing methods of construct validity evaluating, then stated the traits of EFA and CFA, based on them we summarized that using EFA and CFA together is a good way to evaluating the construct validity.
Keywords: measurement and assessment; construct validity; FA; ETA; CFA